2019
DOI: 10.1002/ccd.28506
|View full text |Cite
|
Sign up to set email alerts
|

Previously diagnosed cancer and mortality after ST‐segment elevation acute myocardial infarction treated with primary angioplasty

Abstract: Objective We investigated if a previous cancer diagnosis influences the outcome of patients with STEMI treated with primary coronary intervention (PCI). Background ST‐segment myocardial infarction (STEMI) and a history of cancer can coexist because both have a high incidence and prevalence. Methods Prospective cohort observational study, The primary end‐point was total mortality. Results We included 917 patients, 53 of them (5.8%) were cancer survivors. During follow‐up (median, 643 days [interquartile range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The mean follow-up period in the present study was around 2 years; however, the number of patients in whom follow-up did not reach 5 years was 245 (44.5%) and the remaining 306 (55.5%) patients achieved 5 years follow-up. Followup was longer than in some of the previous studies, 5,9,11, 16 which enabled us to evaluate the effect of a history of cancer on long-term CV events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean follow-up period in the present study was around 2 years; however, the number of patients in whom follow-up did not reach 5 years was 245 (44.5%) and the remaining 306 (55.5%) patients achieved 5 years follow-up. Followup was longer than in some of the previous studies, 5,9,11, 16 which enabled us to evaluate the effect of a history of cancer on long-term CV events.…”
Section: Discussionmentioning
confidence: 99%
“…Some concluded that a history of cancer was associated with a higher risk of CV events, 5-11 while others showed a similar risk between patients with and without a history of cancer. [12][13][14][15][16] This inconsistency among results may be explained in part by the definition of a history of cancer and the limited types of CV events. In some of the previous studies, a history of cancer was defined by questionnaire 14 or self-reporting by the patients, 15 which may have resulted in failure to identify some patients with a history of cancer and thus affecting the results of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also found that all-cause mortality rates were higher in patients with cancer after PCI in general ( 13 ). However, a single-center study reported that there was no survival advantage in patients with STEMI who were treated with PCI compared with the patients who did not have a previous cancer diagnosis ( 14 ). These previous studies focus on the effect of history of cancer on the prognosis of patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…In this current issue of CCI , Iglesias‐Garriz et al reported outcomes in patients with a prior diagnosis of cancer who sustained a STEMI . The timing from cancer diagnosis or treatment to occurrence of STEMI was unknown, but the authors stated that patients with active therapy for cancer were excluded.…”
mentioning
confidence: 99%